A Case Report of Comminuted Mandibular Fracture with Condylar Neck Fracture (Global Journal of Medical Research, 2019)
The fracture of the comminuted type has a prevalence of 30 to 50 % when related to the affecting mandibular bone. They are characterized by the presence of multiple bone involving several lines of fracture, resulting in small fragments within the same area. Treatment modalities for the management of comminuted mandibular fractures include closed reduction, external pin fixation, internal wire fixation, and open reduction and internal fixation using miniplates, titanium mesh tray and screws. The following case report highlights open reduction and internal fixation of a comminuted mandibular fracture in a 24-year-old male patient. The patient treated with open reduction and with a reconstruction plate followed by a short period of maxillomandibular fixation.